Factors influencing support for bat management and conservation in the wildland-urban interface. Issue 2 (4th March 2023) - Petriello, Michael A.; Edgeley, Catrin M.; Chambers, Carol L.; Lee, Martha E.
ABSTRACT: Knowledge, attitudes, and beliefs about bats often underlie social support for bat management and intentions to conserve bats. Effective bat conservation and management hinges on understanding these drivers across contexts. Lands classified as wildland-urban interface (WUI) are rapidly expanding in the USA, increasing the likelihood of human-bat interactions from management practices and encroachment on forested landscapes. We surveyed 410 households in one Arizona WUI community to assess residents' knowledge, attitudes, beliefs, and emotions toward bats, and differences among these variables associated with demographic traits, past encounters with bats, support for bat management, and willingness to place artificial bat roosts on their properties. Greater knowledge and positive attitudes, beliefs, and emotions positively predicted willingness to place roosts 59% to 85% of the time, varying across demographic groups; they did not predict support for bat management. Our findings demonstrated that contexts and demographic traits are important considerations for bat conservation and management.